Coverage Options For Promising Technologies: Medicare's 'Coverage With Evidence Development' - Tunis, Sean R; Pearson, Steven D (Health Affairs, 2006)
In April 2005 the Centers for Medicare and Medicaid Services (CMS) posted on its Web site a draft guidance document describing a new approach to coverage policy called "coverage with evidence development" (CED). CED offered an option for coverage of promising drugs, biologics, devices, diagnostics, and procedures that would not otherwise meet Medicare's evidentiary standards for being "reasonable and necessary." An updated guidance was posted 12 July 2006, clarifying several key statutory, regulatory, and operational issues. This paper traces the history of this policy approach, explains the rationale behind the policy, and describes the major challenges that will need to be addressed for CED to become an important advance in evidence-based coverage decision making.